A 94-GHz planar orthogonal mode transducer. Issue 3 (June 2014) - Berroth, Manfred; Jacob, Arne F.; Schmidt, Lorenz-Peter; Attari, Jawad; Djerafi, Tarek; Wu, Ke
<x content-type="archive" xml:space="preserve">Abstract</x> The orthogonal LSM10 and TE10 modes that are supported by the image SINRD (iSINRD) guide and substrate integrated waveguide (SIW) is exploited to develop a planar millimeter-wave hybrid orthogonal-mode transducer (OMT) within the same dielectric substrate. The two output arms are iSINRD guide and an SIW. The proposed co-layered planar OMT belongs to a narrowband acute angle class. The design process is explained and measurements at 94 GHz are presented. No septa or step changes in thickness are required. Both modes are excited using WR10 transitions, where the transition of one mode is orthogonal to the other. Therefore, the OMT is fabricated as a back-to-back 4-port OMT; two inputs and two outputs for each mode respectively. The lateral dimensions of all guiding arms are 0.6 × 0.635 mm2. An insertion loss of around 1.2 dB is obtained for both LSM10 and TE10 modes, while isolation better than 17 dB is obtained for both modes (30 dB for the LSM10 mode).